Underwater Ambient Noise in a Baleen Whale Migratory Habitat Off the Azores - Romagosa, Miriam; Cascão, Irma; Merchant, Nathan D.; Lammers, Marc O.; Giacomello, Eva; Marques, Tiago A.; Silva, Mónica A. (Frontiers in Marine Science, 2017)
Assessment of underwater noise is of particular interest given the increase in noise-generating human activities and the potential negative effects on marine mammals which depend on sound for many vital processes. The Azores archipelago is an important migratory and feeding habitat for blue (Balaenoptera musculus), fin (Balaenoptera physalus) and sei whales (Balaenoptera borealis) en route to summering grounds in northern Atlantic waters. High levels of low frequency noise in this area could displace whales or interfere with foraging behavior, impacting energy intake during a critical stage of their annual cycle. In this study, bottom-mounted Ecological Acoustic Recorders were deployed at three Azorean seamounts (Condor, Açores, and Gigante) to measure temporal variations in background noise levels and ship noise in the 18–1,000 Hz frequency band, used by baleen whales to emit and receive sounds. Monthly average noise levels ranged from 90.3 dB re 1 μPa (Açores seamount) to 103.1 dB re 1 μPa (Condor seamount) and local ship noise was present up to 13% of the recording time in Condor. At this location, average contribution of local boat noise to background noise levels is almost 10 dB higher than wind contribution, which might temporally affect detection ranges for baleen whale calls and difficult communication at long ranges. Given the low time percentatge with noise levels above 120 dB re 1 μPa found here (3.3% at Condor), we woud expect limited behavioral responses to ships from baleen whales. Sound pressure levels measured in the Azores are lower than those reported for the Mediterranean basin and the Strait of Gibraltar. However, the currently unknown effects of baleen whale vocalization masking and the increasing presence of boats at the monitored sites underline the need for continuous monitoring to understand any long-term impacts on whales.